SPECIFIC ASPECTS OF REFLECTIVE PROCESSES OF PERSONALITIES WITH DIVERSE BODILY EXPERIENCE IN THE CONTEXT OF SELF-DESIGNING - Koliarova, Anastasiia (PSYCHOLOGICAL JOURNAL, 2018)
The article describes the results of the empirical study of the specific aspects of diversity of reflective processes of the personalities, who in certain life circumstances (professional, motivational, state of health) acquired bodily experience, in their ability for self-designing of personality. The conducted empirical study and interpretation of its results are based on theoretical and methodological principles of psychological and hermeneutical approach. Analysis of the scientific literature on the subject of the study enabled to determine specific aspects of forming the bodily experience and developing the study methodology. The ability for self-designing of a personality is considered to be a complex multilevel construction whose core component is an integral body of psychological characteristics of a personality, among which the following are determined: self-conception that is based on self-knowledge, self-awareness and self-identification; subjective control as a personality self-determinacy indicator; life-purpose orientations as a result of purpose-creation and life-creation of a personality; prospective directivity of individual experience of a personality. Appropriate reliable and valid psychodiagnostic techniques were selected for each of the determined factors. Types of reflective processes were detected by means of a reflexivity differential diagnostics technique (D. Leontyev, 2014). The study was conducted on empirically formed samples characterized by various combinations of the existing forms of reflection: “positive reflection”; “all kinds of reflection”; “positive + introspection”; “positive + quasi-reflexion”; “negative reflection”; “unformed reflection”. The ascertainment of intergroup distinctions was conducted by means of realization of statistical Mann-Whitney U-test with paired comparison of all six samples. The statistically defined distinctions based on the findings of the self-conception study enabled to characterize special aspects of samples with diverse reflective processes. According to the results of the analysis of the motivational and blocking influences of the diversity of reflective processes on the development of the ability for self-designing of a personality, one constructive and two non-constructive reflective personality styles are singled out. The constructive reflective style is distinguished in the samples “positive reflection” and “positive + introspection”. Non-constructive reflective styles block the process of development of the ability for self-designing of a personality and have two subspecies: non-constructive reflective style with included quasi-reflective processes (noted in the samples “all kinds of reflections” and “positive + quasi-reflexion”); non-constructive reflective style with unformed positive reflection (noted in the samples “negative reflection” and “unformed reflection”). Prospects for using the results of the study call for the creation of the enriching environment aimed at developing a constructive reflective personality style.